2013
DOI: 10.1002/btpr.1721
|View full text |Cite
|
Sign up to set email alerts
|

Microplates as a microreactor platform for microalgae research

Abstract: High-throughput platforms for microalgae screening are not yet commercially available. In this study, the feasibility of 96-well microplates was analyzed for microalgae research. Equivalence among wells, as culture microreactors, was investigated in controlled high CO2 conditions. Specific growth rates of two microalgae species, Scenedesmus sp. UTEX1589 and an environmental isolate, were significantly higher in border wells than in internal positions. Furthermore, growth rate gradients analyzed as contours thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…In this context, inhomogeneous illumination patterns were described to display problems. Moreover, growth phenotypes, likely induced by ventilation or temperature effects within the incubation chamber (Pacheco et al, ) or uneven CO 2 mass transfer into the wells (Han et al, ), were observed. With regard to extended cultivation times, evaporation control needs to be evaluated carefully, as high liquid loss may distort cultures’ performance (Betts et al, ; Silk et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, inhomogeneous illumination patterns were described to display problems. Moreover, growth phenotypes, likely induced by ventilation or temperature effects within the incubation chamber (Pacheco et al, ) or uneven CO 2 mass transfer into the wells (Han et al, ), were observed. With regard to extended cultivation times, evaporation control needs to be evaluated carefully, as high liquid loss may distort cultures’ performance (Betts et al, ; Silk et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…All known microbial micro-cultivation growth and phenotyping techniques, using liquid or solid media, suffer from biases imposed by the so-called edge effect, where the growth characteristics of the individuals are affected by their position on the plate relative to the edge 16 , 27 . For the techniques involving solid medium, the situation is further complicated by the neighboring colony-imposed effects, which scale with the resolution of the method 1 .…”
Section: Discussionmentioning
confidence: 99%
“…The method proposed here can be used for cultivation and measuring platform, however, we want to highlight the presence of variations associated to plate growth that have been described in this and a previous study (Pacheco et al 2013). The conclusive data analysis must include modeling to control for the temporal and spatial-specific variability inherent to the methodological set-up.…”
Section: Gross Et Almentioning
confidence: 99%
“…Phenotyping of chain-forming phytoplankton the model M1 captured 33% more of the variation than model M0. This result suggested that a substantial proportion of the variation in the data is due to temporal variation (variation between experimental runs), which agrees with previous findings demonstrating variability in microalgal growth on multi-well plate (Pacheco et al 2013).…”
Section: Light Treatmentmentioning
confidence: 99%
See 1 more Smart Citation